SELF-HEALING FOR WOMEN WITH UNWANTED PREGNANCIES AT YAYASAN RUMAH TUMBUH HARAPAN BANDUNG - Tuti Kartika; Arini Dwi Deswanti; Muhammad Ananta Firdaus; Mira Azzasyofia; Vrinsca Paulus (Social Welfare Study Program, 2023)
Abstract. Women who experience unwanted pregnancies (PKTD) face very complex problems: being left behind by the man who impregnated them, being expelled by their families, being stigmatized by society, feeling deep shame and guilt, and losing their future. This study aims to examine the problem of unwanted pregnancy and its solution by RUTH Foundation. The research method is descriptive qualitative with data collection techniques of in-depth interviews, documentation study, observation, and Focus Group Discussion. The results of the study illustrate that the PKTD have problems of shame and fear, loss of future, and being left by the man who impregnated them. This research also succeeded in identifying self-healing services provided by the RUTH Foundation, namely healing carried out by the KTD women themselves with assistance from RUTH Foundation officers. The media used are sewing, knitting, painting, baking, flower arranging, going to nature, and other entertainment media. Self-healing is carried out continuously by emphasizing the willingness and ability of KTD women. The conclusion of this study is that self-healing by the RUTH Foundation has succeeded in leading women with domestic violence to forgive themselves and accept the situation they are in. Forgiving themselves and accepting the conditions experienced has opened up space for women with domestic violence to foster self-motivation and build a fighting spirit to continue a better life. The most important thing is that the Ruth Foundation has saved two generations, namely the CVC herself as a mother and the fetus in her mother's womb. Keywords: Women, unwanted pregnancy, self-healing. Abstrak. Perempuan yang mengalami kehamilan tidak diinginkan (PKTD) menghadapi permasalahan sangat kompleks: ditinggal lelaki yang menghamilinya, diusir keluarga, mendapatkan stigma masyarakat, rasa malu dan bersalah yang mendalam, serta kehilangan masa depan. Studi ini bertujuan mengkaji permasalahan PKTD dan solusinya oleh Yayasan RUTH. Metode penelitian berbentuk deskriptif kualitatif dengan teknik pengumpulan data wawancara mendalam, studi dokumentasi, observasi, dan Focus Group Discussion. Hasil penelitian menggambarkan bahwa PKTD memiliki masalah rasa malu dan takut, kehilangan masa depan, dan ditinggal lelaki yang menghamilinya. Penelitian ini juga berhasil mengidentifikasi pelayanan self healing yang diberikan oleh Yayasan RUTH yakni penyembuhan yang dilakukan oleh perempuan KTD itu sendiri dengan pendampingan dari petugas Yayasan RUTH. Media yang digunakannya adalah menjahit, merajut, melukis, membuat kue, merangkai bunga, pergi ke alam terbuka, dan media hiburan lainnya. Self healing dilakukan secara terus menerus dengan menekankan pada kemauan dan kemampuan perempuan KTD. Kesimpulan penelitian ini adalah bahwa self healing oleh Yayasan RUTH berhasil mengantar perempuan KTD memaafkan dirinya dan menerima situasi yang dialaminya. Memaafkan diri sendiri dan menerima kondisi yang dialami telah membuka ruang bagi perempuan KTD untuk menumbuhkan motivasi diri dan membangun semangat juang melanjutkan kehidupan yang lebih baik. Hal paling penting adalah Yayasan Ruth telah menyelamatkan dua generasi, yaitu PKTD itu sendiri sebagai seorang ibu dan janin dalam kandungan ibunya. Kata kunci: Perempuan, kehamilan tidak diinginkan, self-healing.